Hormetic effect of glyphosate on Urochloa decumbens plants - Moraes, Carolina P. de [UNESP]; Brito, Ivana P. F. S. de [UNESP]; Tropaldi, Leandro [UNESP]; Carbonari, Caio A. [UNESP]; Velini, Edivaldo D. [UNESP] (Taylor & Francis Inc, 2019)
Urochloa decumbens plants may be reached by herbicide drift from applications of glyphosate from neighboring areas or by variations during applications. Considering the different phenological stages and size of plants in these areas, the amount of active ingredient that reaches the plants probably varies. The objective of this study was to evaluate the effects of the application of different doses of glyphosate on U. decumbens plants. Two greenhouse experiments were conducted with two replications at different times. The first experiment evaluated the biological response of U. decumbens plants to glyphosate doses (0, 2.81, 5.63, 11.25, 22.5, 45, 90, 180, 360, 720, and 1,440 g a.e. ha(-1)), with six replications. The second experiment evaluated the response of U. decumbens plants to the application of a selected low dose of 11.25 g a.e. ha(-1). Evaluations of injury were performed at 0, 7, 14, and 21 days after application, and dry weight of plants was determined for each evaluation period. U. decumbens plants increased in dry weight when using the glyphosate dose of 11.25 g a.e. ha(-1). However, plants had different responses to the application of this low dose. It can promote both stimulation and inhibition of plant growth.
Keywords: Growth stimulation; hormesis; morphological parameters